Life cycle assessment of three different management options for spent alkaline batteries - Susana Xará (2015)
The potential environmental impact of Landfilling, Incineration and Recycling of spent household alkaline batteries collected in continental Portugal was compared using LCA methodology and the Recipe Impact Assessment method. Major contributors and improvement opportunities for each system were identified and scenarios for 2012 and 2016 legislation targets were evaluated. For 13 out of the 18 impact categories, the Recycling system is the worst alternative, Incineration is the worst option for 4 and Landfill is the worst option only for one impact category. However if additionally in each system the recovery of materials and energy is taken into account there is a noticeable advantage of the Recycling system for all the impact categories. The environmental profiles for 2012 and 2016 scenarios (25% and 45% recycling rates, respectively) show the dominance of the Recycling system for most of the impact categories. Based on the results of this study, it is questioned whether there are environmental benefits of recycling abroad the household alkaline batteries collected in continental Portugal and, since the low environmental performance of the Recycling system is particularly due to the international transport of the batteries to the recycling plant, is foreseen that a recycling facility located in Portugal, could bring a positive contribution to the environmental impact of the legislation compliance.